Ultrasonic assisted 3D printing of recycled Acrylonitrile Butadiene Styrene (ABS) - Ting, Kung Hieng; Maidin, Shajahan; Ariff, Hambali (Penerbit UTeM Press, 2023)
Additive manufacturing technologies have significantly improved over the past five decades, reducing lead times and material waste in various fields like aerospace, automotive, biomedical, art, civil, and sports. However, waste from printing and human errors is non-biodegradable and requires recycling. This book explores the use of ultrasonic vibration to improve the mechanical properties of recycled ABS filaments printed using an open-source fused deposition modelling printer. This eliminates additional post-processing and costs. The book is divided into five chapters, covering additive manufacturing design, sustainability, ultrasonic vibration application, polymer recycling, feasibility, scientific discovery, and the challenge and future perspective. It is useful for industrial experts, entrepreneurs, university professors, and research scholars.